OpenStack networking cookbook : harness the power of OpenStack networking for public and private clouds using 90 hands-on recipes /: harness the power of OpenStack networking for public and private clouds using 90 hands-on recipes. (2015) - Subramanian, Sriram; Chowdhurry, Chandan Dutta
No abstract available